1997
DOI: 10.1093/mutage/12.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Induction of micronuclei by smokeless tobacco on buccal mucosa cells of habitual users

Abstract: Maras Powder is a kind of smokeless tobacco widely used in lieu of cigarettes in the South-Eastern region of Turkey. In this study, we have evaluated micronuclei in buccal mucosa cells of habitual Maras Powder users. Therefore, we divided our subjects into three groups--smokeless tobacco users, smokers and non-smokers/non-users. The mean percentage of micronucleated (MN) cells was significantly higher in smokeless tobacco users and smokers than in non-smokers/non-users (P < 0.01) [corrected]. The mean percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 8 publications
3
49
1
2
Order By: Relevance
“…Contrary to the findings of Sarto et al and Piyathilake et al, we found that the MN formation was more in users of smokeless tobacco as compared to individuals with smoked tobacco usage [10,11] . An increase in MN count was also associated with smokeless tobacco as studied by Desai et al, Roberts DM and Stich et al, however not in accordance with Ozkul et al, who found no statistically significant variation between users of smoked and smokeless forms of tobacco [12,13,14,15] . We also found a positive correlation between MN frequency and gutkha chewing, which was increased when compared to controls.…”
Section: Discussionmentioning
confidence: 72%
“…Contrary to the findings of Sarto et al and Piyathilake et al, we found that the MN formation was more in users of smokeless tobacco as compared to individuals with smoked tobacco usage [10,11] . An increase in MN count was also associated with smokeless tobacco as studied by Desai et al, Roberts DM and Stich et al, however not in accordance with Ozkul et al, who found no statistically significant variation between users of smoked and smokeless forms of tobacco [12,13,14,15] . We also found a positive correlation between MN frequency and gutkha chewing, which was increased when compared to controls.…”
Section: Discussionmentioning
confidence: 72%
“…Some biomonitoring studies found positive association of age (Ozkul et al,1997;Moretti et al, 2000), sex (Betti et al, 1994;Bajpayee et al, 2002;Fenech et al, 2003), smoking (Burgaz et al, 1999;Hoffmann et al, 2005), alcohol intake (Ramirez et al, 2002) and tobacco chewing (Nair et al, 1991;Trivedi et al, 1993) while some studies observed no association of age (Zhu et al, 1999;Konapaka et al, 2003), sex (Anderson et al, 1993;Zhu et al, 1999;Konapaka et al, 2003), smoking (Moller et al, 2006), alcohol intake (Celik et al, 2007;Martinez-Valenzuela et al, 2009) with genetic damage. In our study, we did not observe any significant association of age, sex and consumption habits (smoking and alcohol use) with genetic damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the region in which this study was conducted, a kind of smokeless tobacco called Maras powder is widely used and only few studies have been done demonstrating its detrimental effects (Erenmemisoglu et al 1991(Erenmemisoglu et al , 1992Erenmemisoglu 1999;Ozkul et al 1995Ozkul et al , 1997Guven et al 2003). Alkaloid composition of the powder which is composed of a plant named N. Rustika L is not much different than N Tobacum L which is a culture tobacco for cigarette, but it has been reported that the content of tobacco is 6-10 fold higher (Shmuk 1953).…”
Section: Discussionmentioning
confidence: 99%